2017
DOI: 10.1103/physrevb.96.104431
|View full text |Cite
|
Sign up to set email alerts
|

Improper ferroelectricity at antiferromagnetic domain walls of perovskite oxides

Abstract: First-principles calculations are performed on magnetic multidomain structures in the SmFeO 3 rare-earth orthoferrite compound. We focus on the magnetic symmetry breaking at (001)-oriented anti-phase domain walls, treating magnetism in the simplest (collinear) approximation without any relativistic (spin-orbit coupling) effects. We found that the number of FeO 2 layers inside the domains determines the electrical nature of the whole system: multidomains with odd mumber of layers are paraelectric, while multido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Yanez-Vilar [7] reported that a polarization may arise as a result of anti-phase AFM domain boundaries, i.e., it does not require non-collinear magnetism or spin-orbit coupling. In addition, Yang reported that an improper polarization originates from an exchange striction mechanism that drives a polar displacement of the oxygen ions located at the magnetic domain walls in SmFeO3 with an orthorhombic structure [9]. Moreover, additional calculations ratified that the mechanism was general among magnetic perovskites with an orthorhombic SmFeO3-like structure.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Yanez-Vilar [7] reported that a polarization may arise as a result of anti-phase AFM domain boundaries, i.e., it does not require non-collinear magnetism or spin-orbit coupling. In addition, Yang reported that an improper polarization originates from an exchange striction mechanism that drives a polar displacement of the oxygen ions located at the magnetic domain walls in SmFeO3 with an orthorhombic structure [9]. Moreover, additional calculations ratified that the mechanism was general among magnetic perovskites with an orthorhombic SmFeO3-like structure.…”
Section: Resultsmentioning
confidence: 95%
“…Until now, several mechanisms have been established for magnetically induced ferroelectricity, such as metal-ligand p-d hybridization, symmetric-exchange striction, and antisymmetric inverse Dzyaloshinskii-Moriya interaction [4][5][6]. In recent years, the polarization induced by the magnetic domain wall has been demonstrated theoretically, such as those occurring in Lu 2 CoMno 6 [7], R 2 NiMno 6 [8] and AFeO 3 (A = Lu, Y, Gd, Sm) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric polarization of domain walls can be the result of several microscopic mechanisms: (i) Dzyaloshinskii-Moriya-like interaction 6 due to spinorbit coupling that is enhanced in Bi-rich sample, 7 (ii) the local decompensation of the antiferroelectric structure in the domain wall, [8][9][10] (iii) the nonrelativistic interaction 11 without involving any spinorbit coupling. In the latest case, the polarization of the domain wall is chirality independent.…”
Section: Electric¯eld-driven Domain Wall Motionmentioning
confidence: 99%
“…In addition, while multiferroicity and ME coupling are most frequently discussed as bulk effects, 2D multiferroics and domain wall multiferroicity, which are so far less addressed but definitely appealing, have been revealed recently [ 7 ]. Even more, while realization of cross-controls of multiple ferroic orders, which offers routes to entirely new device architectures and may bring a revolution in information processing and storage, has been the main stream of multiferroic research, a number of fascinating phenomena not in the main stream but sufficiently compelling, such as non-reciprocity [ 8 , 9 ], topological orders [ 10 ], and thermal Hall effects [ 11 ], have been discovered in multiferroic materials.…”
Section: Introductionmentioning
confidence: 99%